2017
DOI: 10.1002/chem.201701476
|View full text |Cite
|
Sign up to set email alerts
|

2′β‐Fluoro‐Tricyclo Nucleic Acids (2′F‐tc‐ANA): Thermal Duplex Stability, Structural Studies, and RNase H Activation

Abstract: Abstract:We describe the synthesis, thermal stability, structural and RNase H activation properties of 2′β-fluoro-tricyclo nucleic acids (2'Ftc-ANA). Three 2'F-tc-ANA nucleosides (T, 5Me C and A) were synthesized starting from a previously described fluorinated tricyclo sugar intermediate. NMR analysis and quantum mechanical calculations indicate that 2'F-tc-ANA nucleosides prefer sugar conformations in the East and South regions of the pseudorotational cycle. UV-melting experiments revealed that non-consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The cells were incubated for 24 ha t3 78Ci na5% CO 2 atmosphere in the RPMI-1640 medium supplemented with 10 %f etal bovine serum (FBS), vitamins, and antibiotics. After incubation, the cells were transfected with different concentrations of gapmers (1,5,20,50,100,200, 500, 1000 nm)b yu sing Lipofectamine 2000 and incubated for 24 h. Next, the MTT assay was performed. The medium was discarded from the cells, then 150 mLo fM TT solution (0.5 mg mL À1 )i nm edium without phenol red were added.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were incubated for 24 ha t3 78Ci na5% CO 2 atmosphere in the RPMI-1640 medium supplemented with 10 %f etal bovine serum (FBS), vitamins, and antibiotics. After incubation, the cells were transfected with different concentrations of gapmers (1,5,20,50,100,200, 500, 1000 nm)b yu sing Lipofectamine 2000 and incubated for 24 h. Next, the MTT assay was performed. The medium was discarded from the cells, then 150 mLo fM TT solution (0.5 mg mL À1 )i nm edium without phenol red were added.…”
Section: Methodsmentioning
confidence: 99%
“…Previously,i th as been shown that nucleotide conformation and orientation of substituentsp lay an important role for activity.T he incorporation of a3 '-C-hydroxymethyl-arabino nucleotide, with af lexible S-type conformation, or ap iperazino-functionalized-C3'-O2'-linked arabino nucleotide, with ar estricted E-type conformatione nhanced cleavage activity.T he orienta-tion of substituents into the major groove, away from the minor groove were RNase Hi sk nown to bind in aD NA/RNA duplex, was argued as important for tolerability of the modified nucleotides in the initial binding region of RNase H. [1] Combining the 2'-F-ANAm odification with nucleotides that have reduced recognition for RNase Hseems to be asuccessful strategy.H owever,p reviousw ork has established that combining the 2'-F-ANAm odificationw ith the tricyclo-ANAm odification maintainedt he good binding properties and nuclease resistancew hile allowing forRNase Ha ctivation. [5] Selectivity of AON gapmerss hould be of great interest for therapeutic AONs, because off-target effects caused by low specificity potentially lead to toxicity. [10,11] This prompted us to investigate the mismatch discrimination of ON10 with respect to RNase Hc leavage to establish whetheri mproved discrimination towards single-nucleotide polymorphism (SNP) could be observed for ag ap-region-modified antisense gapmer relative to the reference gapmer with an all-DNA gap region.Bymutating one nucleobase at at ime along the 8-mer DNA-based gap region on the complementary RNA, resulting in eight singly mismatched target-RNA strands (T1-T8), the RNase H-induced cleavage patterns were evaluatedr elative to the reference ON8.T he resultsare given in Ta ble2.…”
Section: Cleavage By Rnase Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in the antisense strategy a chemically modified oligonucleotide (antisense oligonucleotide, ASO) recognises a stretch of mRNA through complementary base-pairing and the resulting steric blocks prevents translation [ 116 ]. Alternatively, ASOs can recruit RNase H which catalyses the cleavage of the RNA part of the ASO-mRNA duplex [ 117 , 118 ]. The development of molecules suited for the antisense strategy and gene silencing could serve as new anticancer agents [ 119 ].…”
Section: Ru-dna and The Antigene And Antisense Strategiesmentioning
confidence: 99%